Transcriptional Regulation of Drought Response in Arabidopsis and Woody Plants - Yao, Tao; Zhang, Jin; Xie, Meng; Yuan, Guoliang; Tschaplinski, Timothy J.; Muchero, Wellington; Chen, Jin-Gui (Frontiers in Plant Science, 2021)
Within the context of global warming, long-living plants such as perennial woody species endure adverse conditions. Among all of the abiotic stresses, drought stress is one of the most detrimental stresses that inhibits plant growth and productivity. Plants have evolved multiple mechanisms to respond to drought stress, among which transcriptional regulation is one of the key mechanisms. In this review, we summarize recent progress on the regulation of drought response by transcription factor (TF) families, which include ABA-dependent ABRE/ABF, WRKY, and NF-Y families, as well as ABA-independent AP2/ERF and NAC families, in the model plant Arabidopsis. We also review what is known in woody species, particularly Populus, due to its importance and relevance in economic and ecological processes. We discuss opportunities for a deeper understanding of drought response in woody plants with the development of high-throughput omics analyses and advanced genome editing techniques.